Fecal Microbiota Transplantation as a Novel Therapy for Ulcerative Colitis: A Systematic Review and Meta-Analysis. Issue 23 (June 2016) - Sun, Dali; Li, Weiming; Li, Shumin; Cen, Yunyun; Xu, Qingwen; Li, Yijun; Sun, Yanbo; Qi, Yuxing; Lin, Yueying; Yang, Ting; Xu, Pengyuan; Lu, Qiping
Abstract : Abstract: Variation in clinical evidence has prevented the adoption of fecal microbiota transplantation (FMT) in patients with ulcerative colitis (UC). We aimed to conduct a systematic review and meta-analysis to determine the efficacy and safety of FMT in UC. A systematic literature search was performed in 5 electronic databases from inception through September 2015. Inclusion criteria were reports of FMT in patients with UC. Studies were excluded if they did not report clinical outcomes or included patients with infections. Clinical remission (CR) was defined as the primary outcome. Eleven studies (2 randomized controlled trials (RCTs), 1 open-label case-control study, and 8 cohort studies) with a total of 133 UC patients were included in the analysis. In 11 studies (including 8 noncontrol cohort studies and the treatment arms of 3 clinical control trials), the pooled proportion of patients who achieved CR was 30.4% (95% CI 22.6–39.4%), with a low risk of heterogeneity (Cochran Q test, P = 0.139; I 2 = 33%). A subgroup analysis suggested that no difference in CR was detected between upper gastrointestinal delivery versus lower gastrointestinal delivery. Furthermore, subgroup analysis revealed that there was no difference in CR between single infusion versus multiple infusions (>1) of FMT. All studies reported mild adverse events. FMT is potentially useful in UC disease management but better-designed RCTs are still required to confirm our findings before wide adoption of FMT is suggested. Additionally, basic guidelines are needed imminently to identify the right patient population and to standardize the process of FMT.